Studi In Silico Senyawa Bioaktif Kopi Arabika (Coffea Arabica) Sebagai Kandidat Antikanker terhadap Reseptor PI3K p110-delta subunit - Melani, Fitria; Putri, Silvi Ayudiah; Zulnita, Anis; Latief, Madyawati; Sutrisno, Sustrisno; Tarigan, Indra Lasmana (ALCHEMY:Journal of Chemistry, 2025)
Each year, 9.6 million people lose their lives to cancer, making it the world's second worst killer. Cancer is a disorder that results from genetic changes and has abnormal growth and spreads to other parts of the body. Cancer treatment is currently done with chemotherapy which has unfavorable side effects, so research needs to be done to determine safer alternatives to cancer treatment. This study aims to determine the activity of bioactive compounds in Arabica coffee beans that have potential as anticancer through identification of target receptors and interaction studies using molecular docking methods against PI3K p110-delta subunit receptors. The results showed that of the 21 compounds, five compounds gave good results, namely compounds 4-O-feruloylqunic acid, 4-O-caffeoylqunic acid, gluconic acid, 3-O-feruloylqunic acid and 3-O-caffeoylqunic acid with bond energy (ΔG) and inhibition constant values of -5.47; -5.33; -4.73; -4.69; -4.40 kcal/mol and 98.02; 123.62; 340.97; 363.82; 591.97 μM, respectively. So that these test ligands/compounds can have potential as PI3K receptor inhibitors in cancer treatment